Zoning of coffee growing areas suitable for agricultural mechanization in the State of Espírito Santo - Facco, Alexandro Gomes; Salomão, Bruna Alves; Andrade , Ricardo Guimarães (Seven Editora, 2023)
The State of Espírito Santo has national prominence in terms of coffee production. However, the slope is a limiting factor for the implementation of mechanization. In view of this, the objective was to carry out, based on the slope, the zoning of coffee growing areas suitable for agricultural mechanization in the State of Espírito Santo. The planialtimetric survey used was the Geobases with a resolution of 5m, with the aid of geoprocessing software, the Digital Terrain Model (DTM) was generated and, subsequently, the slope of the coffee growing areas, which were classified according to the mechanization potential of the land: Extremely Suitable (0 - 5%), Very Suitable (5.1 - 10%), Suitable (10.1 - 15%), Moderately Fit (15.1 - 20%) and Not Recommended (> 20%). The state has 428,482.6 thousand hectares of Coffea canephora and Coffea arabica. Being 21.6%; 11.3% and 11.2% with extremely apt, very apt and apt mechanization potential. In addition, 10.7% of the cultivated area was classified as moderately suitable and 45.3% as an area not recommended for mechanized activities. It is also noteworthy that the municipalities with high production of Coffea canephora have the crops with greater aptitude for mechanization when compared to the municipalities that have high production Coffea arabica crops. DOI:https://doi.org/10.56238/sevened2023.006-016